Jembatan Aspirasi: Menghubungkan Suara Anak dengan Kebijakan Melalui Pembentukan Forum Anak Daerah di Kelurahan Nusantara Permai - Agisna Alsa Sabila; Fitri Nurjanah -; Ikhsan Prasetyo; M. Fahreza Akbar; Shifa Indah Maylisari (Jurnal Makkareso, 2026)
The establishment of the Regional Children's Forum in Nusantara Permai Village is a strategic work program aimed at supporting the fulfillment of children's rights and creating a space for children's participation at the village level. This program is implemented with the support of the Women's Empowerment and Child Protection Agency (DP3A), village officials, community leaders, and child representatives from various neighborhood units. Through this forum, children are expected to be able to express their aspirations, organize, and actively participate in regional development processes. The forum's formation was marked by the awarding of pins to core administrators as a symbol of their commitment to championing children's rights and interests. The establishment of the Regional Children's Forum in Nusantara Permai Village is expected to create a child-friendly environment and support the achievement of the Child-Friendly Village program, in accordance with national policy.